Komodifikasi Organ Jaipong di Kabupaten Sumedang - Risna Suryana (PANTUN, 2019)
Organ Jaipong performance is currently becoming a trend in the Sumedang regency. There are pros and cons amomg the artists regarding the Organ Jaipong, yet it still exists in the society. In fact, not few people accept Organ jaipong and invite it to be performed as the entertainment in a wedding ceremony or circumcision. Organ Jaipong is a commodity in the society both for the artists and the lovers. The community considers that Organ Jaipong art is very practical, economical and affordable. It is a solution for the people wanting a performance with minimal budget but the same quality as Bangreng art. The research is aimed to reveal the uses of Jaipong organ for Sumedang society. The study uses descriptive qualitative method applying Vincent Mosco’s commodification theory, 1996, that is by changing the use value into exchange rate. The data are obtained through interview, documentation analysis, field observation, and literature study. The result shows: (1) the Organ Jaipong in Sumedang has been commodified, (2) the commodification of Organ Jaipong in Sumedang is directed for the economy of Sumedang people and the art performers. Organ Jaipong is a commercial art, bought and sold to Sumedang people. Either the art performers or the audience involved in organ jaipong performances is part of the commodity form. This is to improve the economy of the organ Jaipong. The economy is used for daily needs of both the producers and the artists. Keywords: commodification, Organ Jaipong, Sumedang